Diskriminasi Perempuan Korban Konflik Etnis Di Manipur India Dalam Perspektif Hak Asasi Manusia - Hannafiah, Mumtaz; Prawira, M. Rizki Yudha (Universitas Semarang, 2024)
This study aims to analyze the forms of discrimination experienced by Kuki women during the ethnic conflict in Manipur, India, in 2023, and to consider the state's accountability in addressing these issues. The conflict created an environment rife with violence and human rights violations, particularly against Kuki women. There is an urgent need for a deep understanding of the impact of this conflict to demand a swift and effective response to these issues. The research employs a normative legal methodology with a legislative approach and case studies, using international legal instruments as primary sources. The main findings highlight various forms of discrimination and human rights violations, emphasizing the importance of law enforcement and the protection of individual rights. The study also encourages concrete steps to safeguard individual rights and prevent future violations. In conclusion, this research underscores the necessity for a more effective and responsive government response from India in addressing discrimination and human rights violations, particularly against Kuki women in Manipur.Penelitian ini bertujuan untuk menganalisis bentuk-bentuk diskriminasi yang dialami perempuan etnis Kuki selama konflik etnis di Manipur, India, pada tahun 2023, serta mempertimbangkan pertanggungjawaban negara dalam menangani permasalahan ini. Konflik tersebut menciptakan lingkungan penuh kekerasan dan pelanggaran hak asasi manusia, terutama terhadap perempuan etnis Kuki. Dengan urgensi perlunya pemahaman mendalam tentang dampak konflik tersebut untuk menuntut respon yang cepat dan efektif dalam menangani masalah. Metode penelitian hukum normatif dengan pendekatan perundang-undangan dan studi kasus digunakan, dengan instrumen hukum internasional sebagai sumber primer. Temuan utama menunjukan berbagai bentuk diskriminasi dan pelanggaran hak asasi manusia yang terjadi, dengan pentingnya penegakan hukum dan perlindungan terhadap hak-hak individu, serta mendorong langkah-langkah konkret untuk melindungi hak-hak individu dan mencegah terjadinya pelanggaran di masa depan. Sebagai kesimpulan, penelitian ini menekankan perlu adanya respon yang lebih efektif dan responsif dari pemerintah India dalam menanggapi diskriminasi dan pelanggaran hak asasi manusia, terutama terhadap perempuan etnis Kuki di Manipur.